2018
DOI: 10.1016/j.jaap.2018.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature and particle size on structural characteristics of chars from Beechwood pyrolysis

Abstract: This work investigates the effect of temperature and particle size on the product yields and structure of chars obtained from the pyrolysis of Beechwood Chips (BWC), a lignocellulosic biomass. BWC of three different size fractions (0.21-0.50 mm, 0.85-1.70 mm and 2.06-3.15 mm) were pyrolyzed at atmospheric pressure and temperatures ranging from 300 to 900 °C in a fixed bed reactor. Tar and gas yields increased with increasing temperature, while char yield decreased, particularly between 300 and 450 °C. The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(36 citation statements)
references
References 43 publications
4
30
0
2
Order By: Relevance
“…This is due to the mass transfer resistance within the solid that causes volatiles in larger particles to undergo inter-particle reactions to form char before reaching the particle surface. In contrast, least resistance is experienced in smaller particle size, leading to a higher release of volatiles and the formation of liquid and gaseous products with increasing temperatures [16,17]. In this study, the solid yield trend with increasing particle size was found consistent with literatures.…”
Section: Effects Of Feedstock Particle Sizesupporting
confidence: 90%
“…This is due to the mass transfer resistance within the solid that causes volatiles in larger particles to undergo inter-particle reactions to form char before reaching the particle surface. In contrast, least resistance is experienced in smaller particle size, leading to a higher release of volatiles and the formation of liquid and gaseous products with increasing temperatures [16,17]. In this study, the solid yield trend with increasing particle size was found consistent with literatures.…”
Section: Effects Of Feedstock Particle Sizesupporting
confidence: 90%
“…6 showed the parameters obtained from the Raman spectra of biochar produced at different temperatures. The digestate and lignite were rich in the O-containing functional groups and aliphatic structures, which were not likely to be converted into graphite structures at around 900 °C [54,55]. The G band and D band mainly represented the aromatic ring vibration and the aromatic ring polycondensation with 6 or more polymerized aromatic rings instead of graphite and defect structures [53,55].…”
Section: Raman Analysis Of Biocharmentioning
confidence: 99%
“…This phenomenon resulted in an increase in the D and an intrinsic decrease in the h. The particle size was related to the surface area (S). [30][31][32] The particle size distribution for PLN K 2 SO 4 with 0.5% STPP/4% UP varied with crushing time as shown in Table 5. The effect of crushing time on the dissolution time is illustrated in Fig.…”
Section: Rapid Dissolution Of Potassium Sulfatementioning
confidence: 99%